2020
DOI: 10.1089/thy.2019.0707
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Thermal Ablation Techniques for the Treatment of Primary Papillary Thyroid Microcarcinoma: A Systematic Review and Meta-Analysis

Abstract: Background: The increased incidence of primary papillary thyroid microcarcinoma (PTMC) has led to increased research in the field of nonsurgical therapeutic options for those who refuse surgery or are at high risk for surgery. The study aimed at comprehensively evaluating the efficacy and safety of thermal ablation techniques for the treatment of PTMC via a systematic review and meta-analysis. Methods: The Pubmed MEDLINE and EMBASE databases were searched for studies reporting the efficacy and safety of therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 47 publications
5
86
2
Order By: Relevance
“…In terms of safety, all the included studies [21][22][23][24][25][26][27] compared complication rate after the TA or RS and indicated that patients undergoing TA had a low complication rate with a pooled statistically significant difference (3.39% vs 12.94%, p < 0.001). The pooled proportion of complication was similar to a previous meta-analysis of single-arm tests (3.2% for TA) [40]. Voice change is the most common complication after TA and it may be caused by both thermal injury and hemorrhage or other factors such as inflammation, lidocaine injection, and fibrosis around the nerve [42,43].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In terms of safety, all the included studies [21][22][23][24][25][26][27] compared complication rate after the TA or RS and indicated that patients undergoing TA had a low complication rate with a pooled statistically significant difference (3.39% vs 12.94%, p < 0.001). The pooled proportion of complication was similar to a previous meta-analysis of single-arm tests (3.2% for TA) [40]. Voice change is the most common complication after TA and it may be caused by both thermal injury and hemorrhage or other factors such as inflammation, lidocaine injection, and fibrosis around the nerve [42,43].…”
Section: Discussionsupporting
confidence: 83%
“…In the new century, many original articles have explored the efficacy and safety of ablation for treating metastatic lymph nodes from PTMC [36][37][38][39]. Recently, two meta-analysis of single-arm tests also suggested that TA techniques have reasonable safety and efficacy profiles [40,41]. However, studies about the efficiency, safety, and economy of TA for PTMC are limited, and the effect directly compared with RS is worth assessing.…”
Section: Discussionmentioning
confidence: 99%
“…( 114 , 115 ). Minimally invasive US-guided ablation techniques are also being proposed by some groups for nonsurgical treatment of small suspicious nodules ( 119 , 120 ).…”
Section: Managementmentioning
confidence: 99%
“…With the exception of active surveillance and thermal ablation in patients with low-risk microscopic papillary thyroid cancer, the initial management of differentiated thyroid cancer (DTC) mainly relies on surgery followed by radioiodine ( 131 I) remnant ablation (RRA), radioiodine adjuvant therapy (RAT) of potential residual thyroid cancer, or radioiodine treatment (RT) of known disease, under thyroid-stimulating hormone (TSH) suppression (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%